Resolution of the board of directors of the authority No. 171/2014 dated 21/12/2014 concerning the service charges for the entities operating in the activity of microfinance / The Egyptian financial supervisory authority ; translated by The middle east library for economic services. - The Egyptian financial supervisory authority; The middle east library for economic services, translator. (2025)
Egyptian financial supervisory authority resolution of the board of directors of the authority no. 171 of the year 2014 dated 21/12/2014 concerning the service charges for the entities operating in the activity of microfinance الهيئة العامة للرقابة المالية قرار مجلس إدارة الهيئة رقم 171 لسنة 2014 بتاريخ 21/12/2014 بشأن مقابل الخدمات للجهات العاملة فى نشاط التمويل متناهى الصغر